Evaluation and Comparison of Accuracy of Complete Arch Digital and Conventional Implant Impression as Influenced by the Use of a 3D Printed Modular Splint –An In-Vitro Study - Bhushan S. Pol; Ajay V. Sabane; Rajashree D. Jadhav; Pankaj P. Kadam; Arti R. Gachake; Bhagyashree G. Kalsekar (Journal of Pharmacy and Bioallied Sciences, 2024)
Aim: To investigate the accuracy of Complete Arch implant impression digitally and conventionally with and without using a 3D printed modular chain splint. Methods: The STROBE (strengthening the reporting of observational studies in epidemiology) guidelines were use to conduct an analytical cross-sectional study. The total number of samples (n = 40) was derived and was divided into two groups with four subgroups: A1-Digital Impression without splinting of scan bodies (reference scan) and A2-Digital Impression splinted with 3D printed Modular Chain splint (test scan) and B1-Conventional Impression without Splinting of impression copings (reference scan) and B2- Conventional Impression splinted with 3D printed modular chain splint (test scan). In total 40 sample STL files were superimposed. Each analogue were assessed with respect to X, Y and Z axes (X-longitudinal, Y-lateral, and Z-vertical). All the data analysis was performed with SPSS version 22.0 with P < 0.05 as statistical significance. Results: There was no significant difference in the mean standard deviation along the X-axis (P > 0.05). The mean standard deviation along with a Y-axis (P > 0.05) also showed no statistical difference whereas along with the Z-axis mean standard deviation (P > 0.05). Along the vertical Z-axis, there was a significant difference in the mean standard deviation in comparison with the horizontal X and Y axes. Conclusions: There is no significant difference in accuracy of complete arch implant impression when the intraoral digital impression was compared to the traditional impression with or without the use of 3D printed modular splint.